Complementary Medicine for Treating or Preventing Influenza or Influenza-like Illness - Guo, R.; Pittler, M.H.; Ernst, E.
The objective of this review was to assess the evidence for the effectiveness of complementary and alternative therapies for preventing or treating influenza or influenza-like illness, including avian influenza. Systematic literature searches were conducted in 5 databases until June 2006; other data sources included bibliographies of located articles, manufacturers of commercially available preparations, and experts in the field. Randomized clinical trials, controlled against placebo or active comparator, were included. Decisions on inclusion, data extraction, and methodological quality assessment were performed independently by 2 reviewers. Fourteen randomized controlled trials testing 7 preparations were included. For Oscillococcinum, P. quinquefolium extract, Sambucus nigra, and the herbal combination Kan Jang, 2 or more trials reporting some encouraging data were identified. In conclusion, the effectiveness of any complementary and alternative therapy for treating or preventing seasonal influenza is not established beyond reasonable doubt. Current evidence from randomized controlled trials is sparse and limited by small sample sizes, low methodological quality, or clinically irrelevant effect sizes. For avian influenza, no data are currently available. These results strengthen conventional approaches for seasonal influenza.
Keywords: COMPLEMENTARY MEDICINE; INFLUENZA; INFLUENZA-LIKE ILLNESS